Projeto de integraç\~ao do S\~ao Francisco e a segurança hídrica da regi\~ao beneficiada - Monise Terra Cerezini; César Nunes de Castro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The S\~ao Francisco River Transposition Project was proposed by the Federal Government as one of the solutions to overcome water insecurity in part of the Northeast Brazil. This study was proposed with the objective of evaluating water security, in the human, economic, ecosystem and resilience dimensions, and pointing out the possible contributions of the transposition to the water security of the benefited region. Through the Water Security Index (ISH), two scenarios were comparatively evaluated, bringing a current diagnosis and a prospective evaluation based on the possible impacts of the transposition. The human dimension pointed to the risk of water scarcity for a total urban population of 4 million people. The lack of water for irrigated agriculture indicates a risk of 92% of the economic value of its production and the industry sector, whose participation in the local economy is greater, presented 85% of the value of its production at risk in a scenario of water scarcity. The natural and artificial conditions of water reserve indicate water fragility and point to the need to adopt structural and management measures to increase the resilience of this region. In the ecosystem dimension, the impact of ecosystems by the water deficit was evidenced in 46% of the municipalities, in relation to water quality, 81% of the municipalities were classified at the worst level, indicating the critical environmental condition of this region. This investigation identified the most critical areas that need more attention in the search for guaranteeing water supply for populations and economic activities.
10419/284895
Keywords: Q2; Q25; 330; water security; Water Security Index; transposition of the S\~ao Francisco river